Exploring the Use of Adverb ‘Literally’ in Corpus of Contemporary American English - Indah Nur Azizah; Wahya Wahya; Susi Machdalena (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2020)
ABSTRACTThis research aims to describe the use of adverb literally by a native speaker. It is qualitative descriptive research. The main source of this research is the data from one of the online corpora, namely Corpus of Contemporary American English (COCA). There are three steps used in this research, namely the data collection, the data analysis, and the display of the analysis of the results. Based on the data from COCA, this research tries to describe the frequency of the use of adverb literally in COCA and how the adverb is used in the sentence by knowing the particle that follows it. Theories used in this research are the theory of adverb by Pichler (2016) which is supported by the theory by Murphy (1993) and the types of an adverb by Frank (1972). The result shows that the frequency of use of the word literally in COCA amounted to 39.109 contained in the range of 1990 to 2019. The adverb is mostly used in the context of spoken language which is 8.339. The collocation and the concordance lines in COCA are used to find out the particle that follows the adverb literally. The collocation in this research is divided into three classes of words, namely verbs, adjectives, and adverbs. Based on the concordance lines of adverbs in COCA, we can know that the adverb does not have the same position in the sentence. The position of adverb literally can change based on the context of the sentence.